Phytochemical and Antimicrobial Properties of the Aqueous Root Extract of Triclisia dictyophylla - Ajugwo, Anslem O; Ezimah, Anthony C; Awah, Francis M; Mounbegna, Philippe E; Azikiwe, Celestine C (Asian Journal of Medical Sciences, 2013)
Triclisia dictyophylla have been used traditionally for the treatment of different ailments. The root was therefore subjected to phytochemical analysis and antimicrobial/antifungal activity against some hospital-strain disease causing microorganisms. Standard methods were used for the phytochemical screening. The extract was subjected to antimicrobial/antifungal activity using Staphylococcus aureus, Escherichia coli, Klebsiella spp, Pseudomonas aeruginosa and Candida albicans. The sensitivity pattern was compared to that of ciprofloxacin, cotrimoxazole and ofloxacin. Phytochemical analysis revealed mostly alkaloids and protein while tannins, glycoside and saponin were revealed in trace (+) amounts. The extract showed a good antimicrobial activity on Staphylococcus aureus isolated from sputum and on E. coli from both urine and sputum with no antifungal activity. The extract contains active components which could be harnessed for formulation of antibiotics. DOI: http://dx.doi.org/10.3126/ajms.v4i1.7846 Asian Journal of Medical Sciences 4(2013) 15-20